PENGARUH SISTEM PENGUKURAN KINERJA, SISTEM REWARD, BUDAYA ORGANISASI, PEMBERDAYAAN PSIKOLOGIS DAN KEPUASAN KERJA TERHADAP KINERJA MANAJERIAL (Studi Empiris Pada PT Bank Rakyat Indonesia Tbk Kantor Cabang Jambi) - Rahmi Handayani; Afrizal; Junaidi (Jurnal Akuntansi & Keuangan Unja, 2016)
The purpose of this study was to determine and obtain empirical evidence variable that effect managerial performance. variable examined in this study is performance measurement system, reward system, organization culture, psychological empowerment, job satisfaction. Until this research is PT Bank Rakyat Indonesia Tbk branch office in Jambi. Purposive sampling based on the results 44 manager that meet the criteria of the sample. Testing this hypothesis using multiple linear regression analysis. Hypothesistesting resultsshowthat performance measurement, reward system and organization cultureinfluence onmanagerial performance. Hypothesistesting resultsalsoshowthat psycholofical empowermenthas no influence and job satisfaction onmanagerial performance.